2008
DOI: 10.1007/s10549-008-0008-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of life among breast cancer patients three years post-diagnosis

Abstract: Our study provides valuable information for developing strategies/interventions for improving the QOL of breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 56 publications
1
56
1
1
Order By: Relevance
“…It has been suggested that traditionally the breast carries less significance in sexuality and body image in Asian cultures than in Western countries, and that attitudes on changes in body image caused by breast cancer treatment depend on race and social background [20]. The results of this study in Japanese women showed that body image at baseline had no significant effect on the FACT-G, a comprehensive QOL scale.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…It has been suggested that traditionally the breast carries less significance in sexuality and body image in Asian cultures than in Western countries, and that attitudes on changes in body image caused by breast cancer treatment depend on race and social background [20]. The results of this study in Japanese women showed that body image at baseline had no significant effect on the FACT-G, a comprehensive QOL scale.…”
Section: Discussionmentioning
confidence: 53%
“…HRQOL was evaluated in 2232 Chinese patients with breast cancer who enrolled in the Shanghai Breast Cancer Survival Study at 6 and 36 months after diagnosis. Overall HRQOL and physical, psychological and social well-being improved over time, while several factors showed a decline with time, including negative feelings, social support, interpersonal relationships, financial situation and living environment, with a particularly marked worsening of interpersonal relationships [20]. The FACT-G questions concerning social well-being examine relationships with family, partner and friends; therefore, the decreased social well-being found in the current study is similar to the changes observed by Lu et al…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations